2013
DOI: 10.1017/s1049023x13008959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CPAP Treatment Interruption Due to Disasters: Patients with Sleep-disordered Breathing in the Great East Japan Earthquake and Tsunami Area

Abstract: Developing strategies for the continuation of nCPAP therapy during disasters is important for providing healthy sleeping environments for SDB patients in emergency situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…With regard to CPAP usage status, during the Great East Japan Earthquake, a survey within 14 days indicated that 92.3% of 1,047 cases were unable to use CPAP due to power outages due to concerns about aftershocks, relief activities, and loss of equipment, among others. Daytime sleepiness, insomnia, and headache recurred in 25% of 966 cases, indicating the need for measures for continuous use of CPAP in the event of a major disaster [ 173 ].…”
Section: Description Concerning Evidence-based Medicine (Ebm) [ ...mentioning
confidence: 99%
“…With regard to CPAP usage status, during the Great East Japan Earthquake, a survey within 14 days indicated that 92.3% of 1,047 cases were unable to use CPAP due to power outages due to concerns about aftershocks, relief activities, and loss of equipment, among others. Daytime sleepiness, insomnia, and headache recurred in 25% of 966 cases, indicating the need for measures for continuous use of CPAP in the event of a major disaster [ 173 ].…”
Section: Description Concerning Evidence-based Medicine (Ebm) [ ...mentioning
confidence: 99%